Teaching before, during, and after the pandemic: A collaborative autoethnography of college educators teaching service-learning courses - Vergara, Raymond Allan; Blasa-Cheng, Angelique; Vergara, Kimberly Christie; Balatbat, Maricel (Future Science / FSH-PH Publications, 2024)
This is a collaborative autoethnographic account of two educators' experience teaching undergraduate students a course that integrates and activates service-learning principles before, during, and after the pandemic. It is a narrative of the circumstances and problems encountered, how they addressed these issues, and how they addressed problems, resolved issues, and improved learning outcomes. The study also discussed outcomes resulting from the steps they undertook and explored how they want to develop and enhance their courses moving forward. In discussing their experiences, they realized that the pandemic allowed them to reflect on their teaching philosophy and pedagogy, which led to improving their teaching practices. They believe that these improvements led to better learning outcomes. Furthermore, sharing experiences led to discussing unique perspectives on issues and problems, providing insight on how to solve problems, resolve issues, and improve learning outcomes.